Ղունկիանոս Կարնեցու «Աշխատութեան վրայ» բանաստեղծությունը - Հարությունյան, Արիադնա (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Стихотворение ашуга-поэта переходного периода развития армянской литературы Лункианоса Карнеци (1781/1786 –1841) «О труде» имеет познавательный смысл. Одним из свойств ашугской поэзии является периодическое повторение в каждой строке и строфе слова или словосочетания как смысловой единицы, подчеркивающей смысл и суть данного стихотворения. Здесь это слово «դատել» в значении «работать», «трудиться». Карнеци обращается к несущим вдохновение основам духовного облика человека – трудолюбию, мужеству, творчеству. Стихотворение, имеющее так- же признаки светского духа, является одним из примеров развития армянской поэзии. The poem by minstrel-singer of the transitional period in the development of Armenian literature - Ghunkianos Karnetsi (1781/1786-1841), “On Labor” has a cognitive meaning. One of the features of minstrel poetry is the periodic repetition in each line and stanza of a word or phrase as a semantic unit, emphasizing the meaning and essence of this poem. Here the word «դատել» means “to work”, “to labor”. The author refers to the inspirational principles of the spiritual image of a person - diligence, courage, and creativity. The poem, which also has signs of a secular spirit, is one of the examples of the development of Armenian poetry.
Keywords: Գրականագիտություն